2008
DOI: 10.1097/mpa.0b013e31816b30e7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Imaging of Bile Duct Lesions in Autoimmune Pancreatitis

Abstract: Sclerosing cholangitis is one of the extrapancreatic lesions that are commonly detected in AIP patients; it is detected on ultrasonographic imaging as characteristic wall thickening. Our ultrasonographic findings reflect the fact that bile duct wall thickening in AIP is an inflammatory process that responds to prednisolone therapy. Ultrasonography is a useful tool in detecting biliary tract lesions in AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Characteristic bile duct and gallbladder wall thickening was recognized on abdominal ultrasound in 14 (37.8%) of 37 AIP patients. All 14 patients were treated with prednisolone, and this led to immediate resolution of the bile duct lesions [27]. Hyodo et al reported that concentric thickening of the distal common bile duct wall and its strong enhancement by Levovist was a characteristic feature on endoscopic ultrasonography (EUS) (Fig.…”
Section: Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic bile duct and gallbladder wall thickening was recognized on abdominal ultrasound in 14 (37.8%) of 37 AIP patients. All 14 patients were treated with prednisolone, and this led to immediate resolution of the bile duct lesions [27]. Hyodo et al reported that concentric thickening of the distal common bile duct wall and its strong enhancement by Levovist was a characteristic feature on endoscopic ultrasonography (EUS) (Fig.…”
Section: Ultrasonographymentioning
confidence: 99%
“…An association with characteristic right-dominant IBD is suggestive of PSC [23]. If a type 3 or 4 cholangiogram is obtained, cholangiocarcinoma should be discriminated from IgG4-SC by findings of US [27], including EUS [28] or IDUS [29]. The most characteristic IDUS finding in cases of IgG4-SC is wall thickening in areas of the bile duct that do not appear stenotic in the cholangiogram, to allow discrimination from cholangiocarcinoma.…”
Section: Treatmentmentioning
confidence: 99%
“…Because the MRCP can show diffuse thinning of main pancreatic duct [55], non-visualization of the main pancreatic duct on MRCP might suggest narrowing of the main pancreatic duct. Electronic endoscopy may be a useful adjunct to differentiate concentric bile duct thickening (more commonly seen in AIP) from strictures caused by extrinsic compression as seen in pancreatic cancer [56][57]. Kamisawa et al [58] believed that MRCP (1.5 T) could not be used as a substitute for ERCP in the diagnosis of AIP but might be employed for follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound may be a useful adjunct to differentiate concentric bile duct thickening (more commonly seen in AIP and responsive to steroids) from strictures caused by extrinsic compression as seen in pancreatic cancer [42,43]. EUS-guided fine-needle aspiration (FNA) biopsies can confirm the diagnosis of AIP and were performed on 22 of the 23 patients in our study to exclude pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%